CHARACTERIZING THE GROWTH ARREST SPECIFIC GENE, GEM1, IN CHICKEN EMBRYO FIBROBLASTS - Patel, Preyansh (My University, 2023)
Conditions that lead to reversible growth arrest (quiescence), promote the expression of a set of genes called growth arrest specific (GAS) genes. GAS genes play a crucial role in initiating and maintaining the entry into quiescence, while also activating stress responses to help the cell overcome the effects of the stressors. Gene profiling study examining the transcriptome has shown a vast number of genes that are upregulated during quiescence, among them is GEM1 (GTP binding protein overexpressed in skeletal muscle). GEM1 transcripts were elevated 18-fold in response to quiescence. GEM1 is a small monomeric GTPase from the Ras superfamily. It is involved in regulation of cytoskeleton reorganization, and inhibition of voltage gated calcium channels that ultimately prevents hormone secretion. A preliminary study determined that GEM1 is packaged into extracellular vesicles (EV). GEM1 is also reported to promote lipid accumulation and adipogenesis in goat pre-adipocytes. GEM1 is also reported to bind transcription factors that are involved in lipid homeostasis pathways. Thus, it is probable that GEM1 may play a major role in EV formation and/or release, and lipid homeostasis. This study examined the expression of GEM1 at the protein level and validates its candidacy as a GAS gene. We also created two GEM1-shRNA retroviral constructs capable of partially downregulating GEM1 expression which can serve as a molecular tool for further characterizing the function of GEM1 in quiescent CEF.
Keywords: Chicken Embryo Fibroblasts; Growth Arrest Specific Gene; GEM1; GTP-binding protein overexpressed in skeletal muscle